2022
DOI: 10.3390/ijerph19063295
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Parental Styles on Social Skills: The Mediating Role of Affects

Abstract: Parental educational styles have a significant effect in personal development. These styles (authoritative, democratic, permissive and neglectful) can be related to affects and social skills at the individual level. The study presented here, which comprised 456 participants (151 men; 33.11%), with an average age of 22.01 years (s.d. = 2.80), aimed to analyse the relationship between parental styles, affects and social skills, as well as the role played by affects in the relationship between parental style and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 78 publications
2
15
0
7
Order By: Relevance
“…As for emotion regulation, boys are significantly more capable of regulating their emotions than girls. This is similar to the findings of Salavera et al (2022) study. There are some differences in the choice of cognitive emotion regulation strategies between males and females.…”
Section: Gender Differences In Parenting Styles Student-faculty Inter...supporting
confidence: 92%
See 1 more Smart Citation
“…As for emotion regulation, boys are significantly more capable of regulating their emotions than girls. This is similar to the findings of Salavera et al (2022) study. There are some differences in the choice of cognitive emotion regulation strategies between males and females.…”
Section: Gender Differences In Parenting Styles Student-faculty Inter...supporting
confidence: 92%
“…Meanwhile, when parents encourage their children to be independent and meet the need for autonomy, children 10.3389/fpsyg.2022.972006 are more inclined to think proactively and master strategies to cope with difficult situations (Marcone et al, 2020). This leads to a greater sense of self-efficacy, which in turn leads to a better emotion regulation in the face of complex tasks (Salavera et al, 2022). Parents do not blame their children even when they fail and do not break the family atmosphere where children are supported and respected (Moè et al, 2020).…”
Section: Parenting Styles and Emotion Regulationmentioning
confidence: 99%
“…Navarro et al (2019) In contrast, children of parents who exercise positive parenting practices are less likely to experience internalizing and externalizing problems and more likely to engage in prosocial behavior (Sangawi et al, 2018). Research shows that negative parenting practices make children more likely to develop emotional and behavioral problems (Fong et al, 2022;Salavera et al, 2022). Authoritative parents are nurturing, responsive and supportive parents set clear expectations and boundaries for their children and ensure they understand why they are in place.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, democratic parenting style was not included in the final regression model in the study, but univariate analysis results showed that only democratic parenting style was associated with reduced FC risk. The democratic style is characterized by respect for children, autonomy, and the promotion of desirable behavior, and creating a democratic environment and emotional warmth [ 28 ]. The children in these households tend to develop good social skills and a healthy mental environment (e.g., good self-control, self-esteem and initiative), which reduces the risk of children FC [ 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%